Evaluating User Experience in a Microservices-Based E-Learning Platform for Technopreneur ship with the UEQ - Lokapitasari, Poetri Lestari; Patmanthara, Syaad; Ashar, Muhammad; Kurniawan, Fachrul (International Journal of Engineering, Science and Information Technology, 2025)
This paper evaluates the user experience of a microservices-based e-learning platform created for technopreneurship education using the User Experience Questionnaire (UEQ). Microservices present new chances to improve system performance, dependability, and learner involvement when educational systems choose modular and scalable designs. The study presents a benchmarking strategy by contrasting the newly created platform with two extensively utilized commercial platforms, Shopee and Tokopedia, which both use scale microservices. Fifty undergraduates participated in the study and evaluated six fundamental UX dimensions: attractiveness, perspicuity, efficiency, dependability, stimulus, and novelty. Quantitative research shows that the e-learning system works well in terms of pragmatic quality (clarity, efficiency, and reliability) and hedonic quality (stimulus and creativity). Comparatively, in perspicuity and efficiency, T-test comparisons reveal statistically significant benefits of the e-learning platform over Tokopedia; similarly, in stimulation and novelty, over Shopee. These findings imply that the microservices-based design improves emotional involvement and perceived innovation in the learning environment and supports functional performance. The study indicates that tools usually used in commercial environments allow one to assess user experience in education effectively. It also emphasizes how the design of learner-centred digital platforms can be guided by benchmarking against industry systems. The results provide helpful information for teachers trying to match educational technologies with user expectations moulded by actual digital experiences and for e-learning developers.